Pedestrian Fatalities and Their Demographic Disparities in the US - Juliana Panhorst; Alyssa Ryan (Findings)
Using a Center for Disease Control and Prevention dataset, we analyzed how sex, age group, ethnicity, race, and urbanization level are linked to pedestrian fatality rates from 2011 to 2019. Outcomes in some subgroups had a higher death rate than other subgroups across sexes. For example, males who identify as American Indian or Alaska Native (OR = 1.98) as well as males who were 85 years and older (OR= 2.14) had the highest annualized death rates.